The biomechanics of rowing - a unique insight into the technical and tactical aspects of elite rowing - Kleshnev, V. (Crowood, 2020)
n rowing, races are often won in spite of, not because of, technique, and many misconceptions still preoccupy both rowers and coaches. This book explains the facts about rowing technique and will help you to find the right way to achieve your best performance. In this new edition, comprehensively updated to take account of the most recent developments in the sport it offers a unique insight into the technical and tactical aspects of rowing, based on over twenty-five years experience of working with the best rowers and coaches worldwide, a careful analysis of millions of data samples, and comprehensive biomechanical modelling with the aim of finding an optimal balance of variables.